2010
DOI: 10.5212/olharprofr.v.13i2.0005
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos de consumo entre catadores de materiais recicláveis: uma abordagem metodológica

Abstract: Resumo: Considerando a profi ssão de catador bastante emblemática para discutirmos a respeito do tema "hábitos de consumo" e suas diversas facetas (ambientais, sociais, políticas, educacionais), procuramos conhecer o que os catadores de uma determinada cooperativa de reciclagem pensam sobre consumo: como e o que consomem, como gastam o que recebem com a reciclagem de materiais, o que consideram essencial e o que consideram desnecessário em termos de consumo. A pesquisa consistiu em ouvir a opinião dos indivídu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Furthermore, it was observed that there are few studies directed towards female work in recycling, a fact which does not converge with evidence of the striking presence of women in this scenario. [7][8] Finally, emphasis is placed on the incipient presence of nursing in the production of knowledge regarding recycling workers' health, a presence which is necessary, bearing in mind that nursing has an ethical commitment to the health and quality of life of the community, having as a principle the promotion of the human being as a whole, meeting the precepts of ethics and of bioethics. 9 Within this perspective, this study's objective was to reveal the recognition of the work and its meanings and the perception of female recycling workers of a recycling cooperative.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was observed that there are few studies directed towards female work in recycling, a fact which does not converge with evidence of the striking presence of women in this scenario. [7][8] Finally, emphasis is placed on the incipient presence of nursing in the production of knowledge regarding recycling workers' health, a presence which is necessary, bearing in mind that nursing has an ethical commitment to the health and quality of life of the community, having as a principle the promotion of the human being as a whole, meeting the precepts of ethics and of bioethics. 9 Within this perspective, this study's objective was to reveal the recognition of the work and its meanings and the perception of female recycling workers of a recycling cooperative.…”
Section: Introductionmentioning
confidence: 99%